The Impact of Renewable Energy Policies on Sustainable Economic Growth: Applied Study in China, India, Brazil, and Mexico - Nadia Khutheir Ganawi; Sundus Jasim Shaaibith (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research aims to examine the impact of renewable energy policies on sustainable economic growth in four emerging countries: China, India, Brazil, and Mexico. The importance of the study comes in light of the global shift towards clean energy, and the efforts of developing countries to achieve a balance between the requirements of economic development and environmental commitments. The study relies on a descriptive analytical approach supported by a comparative method, where the policies adopted in each country are analyzed and compared with the indicators of economic performance and environmental sustainability during the period (2015-2024). The study is based on official data from international institutions such as the World Bank and the International Energy Agency. The results indicate a positive correlation between the intensity of the implementation of renewable energy policies and the achievement of sustainable economic growth, especially in countries that have provided a supportive legislative and institutional environment for investment in this sector. National experiences have also shown varying levels of impact, with China and Brazil recording more stable results thanks to the clarity and continuity of their strategies. The research endorses that renewable energy policies must be integrated with industrial growth, education and technology rules to expand their impact and achieve a more sustainable economic change in emerging countries.